Poder legislativo e educação no Pará: produção legislativa sob restrições institucionais (13ª e 14ª legislaturas) - CARDOSO, Adalberto Trindade (2007)
This is a study of the legislative production in education carried through in the State legislature of the State of Para in the period that corresponds its 13th and 14th legislatures (1995-2002). The objective of the work was to identify to the type legislative activity that state parliamentarians had developed in the educational area in the ALEPA by means of the analysis of the profile of the distribution of benefits that they had intended to make with this production and of the factors that intervened in its definition. The initiative of this research was provoked for the predominant consideration concerning the parliamentary performance that attributes to an essentially distributive character (clienteles) in the concession of benefits in sight of returns politicians to it (electoral). Thus, the analysis was confronted with two empirical problems of inquiry: first, to discover which the profile of benefits that them state parliamentarians had looked for to grant in education by means of legislative production e, second, as to explain its emergency in the context of the studied legislatures? In this direction, the work was divided in two parts: in the first one it became the survey of the data of the legislative proposals in the educational area in the ALEPA in the indicated period. For the analysis of the profile of benefits it was used theory of the legislative decisions; the result was collated, in the second part, with the main explicative approaches of the parliamentary behavior. One concluded that, in contrast of the predominantly perspective, the profile of distribution of benefits found, did not present an essentially distributive character, however, its importance is secondary in the constitution of the educational legislation of the State, therefore the factors that intervene in its definition elapse of the institutional restrictions that conform the space of the legislative production in education in the ALEPA, which structuralize the strategic options of them parliamentarians stimulating an performance, in this scope, of not distributive character, however, on the other hand, it removes them the possibility to intervene with the educational policy.